2019
DOI: 10.1159/000505872
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism Delays Expression of Alzheimer’s Clinical Syndrome

Abstract: Objective: To evaluate the effects of bilingualism on the emergence of Alzheimer's clinical syndrome. Background: Studies have proposed an increase in cognitive and neural reserve from the management and control of two languages, with a consequent delayed expression of dementia. Methods: In a clinic with a large immigrant population, we identified 253 patients with probable Alzheimer's disease (AD) with intermediate or high evidence of AD pathophysiological process. These patients were reviewed for demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Bilingualism seems to have an impact on cognitive functioning at all ages (71). Importantly, L2 acquisition might be a factor promoting compensatory reserve and delaying cognitive decline in dementia (72). Individuals intensively learning L2 over 3 months show a significant increase in hippocampus volume and cortical thickness in the left middle frontal gyrus, inferior frontal gyrus, and superior temporal gyrus (73).…”
Section: Perspectivesmentioning
confidence: 99%
“…Bilingualism seems to have an impact on cognitive functioning at all ages (71). Importantly, L2 acquisition might be a factor promoting compensatory reserve and delaying cognitive decline in dementia (72). Individuals intensively learning L2 over 3 months show a significant increase in hippocampus volume and cortical thickness in the left middle frontal gyrus, inferior frontal gyrus, and superior temporal gyrus (73).…”
Section: Perspectivesmentioning
confidence: 99%
“…Other recent retrospective studies provide corroborative evidence: for instance, Zheng et al (2018) found a 7-year delay of AD onset in Cantonese/Mandarin bilingual older adults as compared to Cantonese and Mandarin monolingual peers. Finally, a study by Mendez et al (2019) replicated the finding of a 4-year AD delay in a sample of bilingual seniors who spoke various first languages (L1s) and English as a second language (L2).…”
Section: Effects Of Bilingualism On Pathological Agingmentioning
confidence: 73%
“…Consistently with previous literature, clinical manifestation of AD appeared to be delayed by 4.6 years in bilingual patients. More recent studies confirmed bilingualism's effect on the delay of AD onset: Zheng et al (2018) reported a 7-year delay in Cantonese/Mandarin bilinguals as compared to both Cantonese and Mandarin monolinguals, while Mendez et al (2020) reported a 4-year delay in a sample of bilinguals with different L1s and English as an L2. Moreover, Perquin et al (2013) examined 232 senior multilinguals in Luxembourg who were either classified as healthy or affected by mild cognitive impairment (MCI).…”
Section: Neuroprotection During Pathological Agingmentioning
confidence: 81%